A Mini Review: The History of Yeast Flocculation with an Emphasis on Measurement Techniques. (2nd October 2021) - Mehta, Devanshu V.; Curtis, Savanna J.; Rudolph, Arthur B.; Mary, Colette St.; Goodrich, Renee; Schneider, Keith R.; MacIntosh, Andrew J.
Abstract: Flocculation of yeast is a natural phenomenon wherein cells clump together and come out of suspension. This is often relied upon by brewers as a natural means of removing yeast, as clumps of yeast cells (flocs) typically precipitate from the fermentation vessel. A problem that has long frustrated brewers is when yeast flocculation does not proceed as expected. This has been linked to a fermentation's premature ending ("hung" fermentation). Since the early 1900s, researchers have explored numerous methods to identify the flocculation characteristics of yeast. Traditional methods have contributed to an understanding of the fundamentals of flocculation by assessing the impact of stressors (e.g., pH, temperature, wort density and composition, and ethanol content) on the flocculence of yeast. In 1994, conventional measurement techniques were combined with modern technology to develop the American Society of Brewing Chemist's method "Yeast 11, " which was revised by the society in 2011. This method succeeded in the identification and definition of the flocculence characteristics of particular yeast strains but has not taken into account the changes in flocculation tendency over time for later generations of the same yeast strain. The ASBC also describes a fermentation assay to assess aberrant yeast behavior such as premature yeast flocculation (PYF) in the "Yeast 14" method. The current challenge in flocculation research is understanding the changing genetics of flocculation throughout the usage of a yeast strain in a fermentation process. This review details the evolution of yeast flocculation measurement, our current understanding, and potential future developments.